Divergence in metabolomic profile in clownfish and damselfish skin mucus - Heim, Sara; Teav, Tony; Gallart-Ayala, Hector; Ivanisevic, Julijana; Salamin, Nicolas (Frontiers in Ecology and Evolution, 2023)
The clownfish - sea anemone mutualism was suggested to have triggered the adaptive radiation of clownfishes, but the origin of clownfish resistance to stinging tentacles of host anemones remains unclear. The presence of specific compounds in the mucus of clownfishes conferring them the unique ability to prevent nematocyst discharge from their hosts has been the most supported hypothesis. Yet the mystery regarding the types of compounds found in clownfish skin mucus remains unsolved. We analyzed the chemical composition of clownfish and damselfish mucus using a metabolomics and lipidomics approach, to describe key molecular differences between these closely related fish yet ecologically different. The polar and lipid metabolome signatures were highly specific and allowed to discriminate between the clownfish and damselfish clades. The most discriminative part of the signature was the sphingolipid profile, displaying a broader diversity of ceramides present in significantly higher levels in clownfish mucus. Importantly, the inter-specific variability of metabolic signature was significantly higher in clownfishes, although their diversification is evolutionarily more recent, thus implying the impact of symbiosis on metabolic variability and adaptation. Furthermore, specialists and generalists clownfish species displayed distinctive metabolite signature. Two strict clownfish specialists, which are phylogenetically distant but share the same host species, clustered together based on their molecular signature, suggesting a link with their mutualistic nature. Overall, comparative analyses of metabolic signatures highlight differences in chemical composition of clownfish mucus and provide insight into biochemical pathways potentially implicated in clownfish adaptation to inhabit sea anemones and consequently diversify.